RNA pathogenesis via Toll-like receptor-activated inflammation in expanded repeat neurodegenerative diseases - Richards, Robert I.; Samaraweera, Saumya; van Eyk, Clare; O'Keefe, Louise V.; Suter, Catherine (Frontiers in Molecular Neuroscience, 2013)
Repeat sequences that are expanded in copy number are the basis for ~20 dominantly inherited neurodegenerative diseases, including Huntington’s Disease. Despite some of the responsible genes being identified as long as 20 years ago, the identity and nature of the disease-causing pathogenic pathway remains a gap in knowledge for these diseases. This understanding is essential for rational approaches to delay onset, slow progression or ultimately effect cure. We have previously hypothesized that an RNA-based pathogenic pathway has a causal role in the dominantly inherited unstable expanded repeat neurodegenerative diseases. In support of this hypothesis we, and others, have characterized rCAG.rCUG100 repeat double-strand RNA (dsRNA) as a previously unidentified agent capable of causing pathogenesis in a Drosophila model of neurodegenerative disease. Dicer, Toll and autophagy pathways have distinct roles in this Drosophila dsRNA pathology. Dicer-dependence is accompanied by cleavage of rCAG.rCUG100 repeat double-strand RNA down to r(CAG)7 21-mers. Among the ‘molecular hallmarks’ of this pathway that have been identified in Drosophila, some [i.e. r(CAG)7 and elevated TNF] correlate with observations in affected people (e.g. HD, ALS) or in related animal models [i.e. autophagy]. The Toll pathway is activated in the presence of repeat-containing double-stranded RNA and toxicity is also dependent on this pathway. How might the endogenously expressed dsRNA mediate Toll-dependent toxicity in neuronal cells? Endogenous RNAs are normally shielded from Toll pathway activation as part of the mechanism to distinguish ‘self’ from ‘non-self’ RNAs. This typically involves post-transcriptional modification of the RNA. Therefore, it is likely that rCAG.rCUG100 repeat double-strand RNA has a characteristic property that interferes with or evades this normal mechanism of shielding. We predict that repeat expansion leads to an alteration in RNA structure and/or form that perturbs RNA mod